2023
DOI: 10.7150/ijms.78428
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 promotes angiogenesis in peritoneal dialysis by epigenetically activating SP4 expression in the IL-6/sIL-6R signalling pathway

Abstract: Background: Interleukin-6 (IL-6)/soluble IL-6 receptor (sIL-6R) promotes peritoneal angiogenesis by stimulating SP4-mediated vascular endothelial growth factor (VEGF) production in peritoneal dialysis (PD). Moreover, histone methyltransferase enhancer of zeste homologue 2 (EZH2) is involved in IL-6/sIL-6R signalling via the acceleration of vascular endothelial growth factor (VEGF)-induced angiogenesis. However, the molecular mechanism underlying how EZH2 epigenetically activates VFGF expression in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In a recent study, SP1 was confirmed to mediate the impact of miR-335-5p on the phenotypic switching of VSMCs in AAD, exhibiting a pro-apoptotic influence by repressing the expression of p21WAF1/Cip1 at the transcriptional, mRNA, and protein levels [ 50 , 51 ]. Additionally, SP1 and SP4 have been recognized as key TFs involved in the regulation of vascular endothelial growth factor (VEGF) production by binding to specific sites in the VEGF promoter [ 52 , 53 ]. KLF7's involvement in various cardiovascular diseases is well-documented.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, SP1 was confirmed to mediate the impact of miR-335-5p on the phenotypic switching of VSMCs in AAD, exhibiting a pro-apoptotic influence by repressing the expression of p21WAF1/Cip1 at the transcriptional, mRNA, and protein levels [ 50 , 51 ]. Additionally, SP1 and SP4 have been recognized as key TFs involved in the regulation of vascular endothelial growth factor (VEGF) production by binding to specific sites in the VEGF promoter [ 52 , 53 ]. KLF7's involvement in various cardiovascular diseases is well-documented.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24][25] Among these cytokines, IL-6 is a pleiotropic cytokine involved in epithelial and immune cell angiogenesis, proliferation, and differentiation. [26][27][28][29] Owing to its excessive activation and dysregulation of receptor signaling in T cells, IL-6 is involved in the pathogenesis of psoriasis. [30][31][32][33] IL-6 contributes to the differentiation and maintenance of T helper (Th) 17 cell development and function and inhibits regulatory T cell (Treg) differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…The upregulation of other cytokines, such as IL‐6, IL‐12, IL‐22, IL‐29, IL‐36, IL‐1 β, and tumor necrosis factor‐α, is also involved in the pathogenesis of psoriasis 20–25 . Among these cytokines, IL‐6 is a pleiotropic cytokine involved in epithelial and immune cell angiogenesis, proliferation, and differentiation 26–29 . Owing to its excessive activation and dysregulation of receptor signaling in T cells, IL‐6 is involved in the pathogenesis of psoriasis 30–33 .…”
Section: Introductionmentioning
confidence: 99%